Problems of achieving legal efficiency in the consideration of class actions - E. S. Trezubov; N. S. Zvyagina (Правоприменение)
The paper examines the procedure for considering a class action in the Russian civil procedure in order to identify obstacles to the effective application of this institution. In developed foreign legal orders, group proceedings are a popular socially significant jurisdictional procedure for considering a large number of the same type of requirements, which allows optimizing the burden on the judicial system, ensuring the achievement of legal certainty and the effectiveness of judicial protection. As a result of the reform of group production, an institution sui generis appeared, which differs in many respects from foreign analogues. Given that group proceedings in Russia are still not in demand, the authors has identified obstacles to the intensification of this procedure, many of which indicate a superficial regulation of the procedural form.The study used comparative legal, formal logical and systemic structural methods, which made it possible to give a comprehensive assessment of the identified gaps in the legal regulation of group proceedings in Russian civil, commercial and administrative litigation. The first of the identified problems is related to the lack of regulatory rules for certification of a group of persons. To initiate proceedings on a class action, it is necessary to join a significant number of co-plaintiffs, whose claims are based on homogeneous legal and factual circumstances. However Russian procedural codes do not regulate the criteria by which certification of a group should be carried out, and also do not establish rules for accepting a court ruling on preparing a case for trial, allowing members to subsequently authorize. It is noted that for effective group proceedings it is necessary to issue an appropriate definition, which would define the criteria for the homogeneity of the grounds for claims and the method of protecting the violated right chosen by the applicant. The law should directly provide for the possibility of appealing against such a judicial act. Also, for the purposes of joining the requirements to protect the interests of a group of persons, it is proposed to publish a notice on the initiation of proceedings not only on the websites of the court and the defendant, but also in the official media.The problems of implementing the qualities of the legal force of a court decision on a class action, such as exclusivity and prejudice, are also identified, since the law allows challenging the circumstances established when considering a class action when considering a personal claim of a member of a class who has not joined a class action in the future.